Gender Issues in Islamic Law and Their Implications for Human Rights - Suud Sarim Karimullah (Prodi Hukum Ekonomi Syariah (Muamalah), 2026)
This study explores the complexity of gender issues in Islamic law and their impact on human rights in the context of the Muslim world to uncover patterns of gender inequality that persist in law and social practice in various Muslim societies. This study is based on the literature study method with an approach to literature analysis carried out in an integrative and comprehensive manner. The results highlight the importance of a deeper understanding of gender issues in Islamic law and their implications for human rights in efforts to achieve a more inclusive society and respect for human rights for all individuals in the Muslim world. Despite an Islamic legal framework that provides the potential for gender equality and the protection of human rights, patriarchal interpretations and unequal practices still dominate in many cases. The impact of Islamic legal practice on human rights, especially women and minorities, often involves violations of fundamental rights such as freedom of religion and equality in the eyes of the law. However, there are also efforts to reform Islamic law that focus on more inclusive interpretations and support for human rights, raising hopes for positive future change.